Partial Edentulism Based on Kennedy’s Classification (Medical Forum Monthly, 2024)
Objective: The aim of this study is to investigate the distribution of the partial edentulism in general population according to Kennedy’s classification.Study Design: Cross Sectional StudyPlace and Duration of Study: This study was conducted Isra Dental College OPD in Hyderabad from Feb 2010 to July 2011.Materials and Methods: This is a cross sectional study carried out on 395 subjects, both males and females and belonging to age groups 35-50 years, completed during the period of one and half year. All patients’ personal history was taken regarding their age and socioeconomic condition. Partial edentulism was recorded by visually examining the study sample.Results: The results include the visual examination of 395 individual in which majority were males 246 (62 %), mostly belonging to the poor class , 231 (59 %) and in early forties 181(46%). There is high prevalence of Kennedy’s class IV, 128(32 %) among sample then followed by Kennedys Class I 92(23.3%), II 76(19.2%) and III 50(12.7%). The association between partial edentulism according to Kennedy’s classification with socio-demographic profiles of the sample is statistically significant (68, 17%; p=0.04).Conclusion: In our study there is significant difference between gender and partial edentulism as more male patients visit the dental clinic for partial denture belongs to low income status and in 41-45 years age group.